Bio-Fabrication of Silver Nanoparticles Using Citrus aurantifolia Fruit Peel Extract (CAFPE) and the Role of Plant Extract in the Synthesis - Tijjani Mustapha; Nur Raihana Ithnin; Hidayatulfathi Othman; Zatul Iffah Abu Hasan; Norashiqin Misni (MDPI, 2024)
Indexed by WOS